VOC sensing using batch-fabricated temperature compensated self-leveling microstructures - Likhite, Rugved; Banerjee, Aishwaryadev; Majumder, Apratim; Karkhanis, Mohit; Kim, Hanseup; Mastrangelo, Carlos H. (Sensors and actuators. B, Chemical, 2020)
[Display omitted] •Intrinsic temperature compensation mechanism based on mechanical self-leveling.•No externally powered temperature compensation electronics required.•Significant improvement to simple microcantilever type vapor sensors.•Polyimide, Polyurethane and PDMS polymers used for the detection of VOCs.•Target identification using Support Vector Machine algorithm. We present the design, fabrication, and response of a low-power, polymer-based VOC sensor based on the self-leveling of mechanically leveraged structures. The device utilizes folded polymer-coated microcantilevers to achieve passive temperature compensation without the need for additional compensating sensors or electronics. We demonstrate that a self-leveling vapor sensor provides the same gas response as a simple microcantilever geometry, showing ∼20 % change in device capacitance when subjected to 35–85 %RH change while showing nearly-zero baseline drift due to changes in ambient temperature when the temperature is increased from 23−72 °C which is ∼52-fold better than a simple microcantilever geometry. The response of the VOC sensor was measured using three polymers (Polyimide, Polyurethane, and PDMS) against five different analytes (Ethanol, Acetone, Benzene, Hexane, and Water) and an SVM-based model was used to show target specificity. The sensor also showed an absorption response time (τ90) of ∼138 s. We propose that the self-leveling vapor sensor geometry is a significant improvement to a simple microcantilever vapor sensor as it offers the same performance but shows near-complete elimination of temperature-induced baseline drift.